A hybrid unsupervised—Deep learning tandem for electrooculography time series analysis - Stoean, Ruxandra; Stoean, Catalin; Becerra-García, Roberto Antonio; García-Bermúdez, Rodolfo; Atencia-Ruiz, Miguel Alejandro; García-Lagos, Francisco; Velázquez-Pérez, Luis; Joya-Caparrós, Gonzalo (PLOS, 2020)
Medical data are often tricky to get mined for patterns even by the generally demonstrated successful modern methodologies of deep learning. This paper puts forward such a medical classification task, where patient registers of two of the categories are sometimes hard to be distinguished because of samples showing characteristics of both labels in turn in several repetitions of the screening procedure. To this end, the current research appoints a pre-processing clustering step (through self-organizing maps) to group the data based on shape similarity and relabel it accordingly. Subsequently, a deep learning approach (a tandem of convolutional and long short-term memory networks) performs the training classification phase on the ‘cleaned’ samples. The dual methodology was applied for the computational diagnosis of electrooculography tests within spino-cerebral ataxia of type 2. The accuracy obtained for the discrimination into three classes was of 78.24%. The improvement that this duo brings over the deep learner alone does not stem from significantly higher accuracy results when the performance is considered for all classes. The major finding of this combination is that half of the presymptomatic cases were correctly found, in opposition to the single deep model, where this category was sacrificed by the learner in favor of a good accuracy overall. A high accuracy in general is desirable for any medical task, however the correct identification of cases before the symptoms become evident is more important.
Keywords: Aprendizaje automático (Inteligencia artificial); Informática médica; Redes neuronales artificiales; Spino-cerebral ataxia of type 2; Electrooculography; Computational diagnosis; Self-organizing maps; Convolutional neural networks; Long short-term memory networks